Do people with musculoskeletal pain differ from healthy cohorts in terms of global measures of strength? A systematic review and meta-analysis. (February 2023) - Verdini, Enrico; Maestroni, Luca; Clark, Michael; Turner, Anthony; Huber, Jörg
Objective: It is currently unknown if people with musculoskeletal pain display different multi-joint strength capacities than healthy cohorts. The aim was to investigate whether people with musculoskeletal pain show differences in global measures of strength in comparison to healthy cohorts. Data sources: A systematic review was conducted using three databases (Medline, CINAHL and SPORTDiscus) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Review methods: Studies involving participants with painful musculoskeletal conditions and multi-joint strength assessment measured at baseline were included. A meta-analysis was also performed to compute standardized mean differences (± 95% confidence intervals), using Hedge's g, and examined the differences in multi-joint strength at baseline between participants with painful musculoskeletal conditions and healthy participants. Results: In total, 5043 articles were identified, of which 20 articles met the inclusion criteria and were included in the qualitative analysis. The available evidence revealed that multi-joint strength values were limited to knee osteoarthritis, fibromyalgia, chronic low back pain, and rheumatoid arthritis. Only four studies were included in the quantitative synthesis and revealed that only small differences in both chest press ( g  = −0.34, 95% CI [−0.64, −0.03]) and leg press ( g  = −0.25, 95% CI [−0.49, −0.02]) existed between adult women with fibromyalgia and active community women. Conclusion: There is a paucity of multi-joint strength values in participants with musculoskeletal pain. Quantitative comparison with healthy cohorts was limited, except for those with fibromyalgia. Adult women with fibromyalgia displayed reduced multi-joint strength values in comparison to active community women.